Effect of praseodymium doping on electroresistivity along c-axis in Y₁₋xPrxBa₂Cu₃O₇₋δ single crystals - Vovk, R.V.; Vovk, N.R.; Samoilov, A.V. (Functional Materials, 2013)
In the present study influence of praseodymium doping on conductivity across (transverse) the basal plane of high-temperature superconducting Y₁₋xPrxBa₂Cu₃O₇₋δ single crystals is investigated. It is determined that increase of praseodymium doping leads to increased localization effects and implementation of the metal – insulator transition Y₁₋xPrxBa₂Cu₃O₇₋δ, which always precedes the superconducting transition. The praseodymium concentration increase also leads to significant displacement of the point of the metal – insulator transition to the low temperature region.